Synergistic Enhancement of Targeted Wound Healing by Near-Infrared Photodynamic Therapy and Silver Metal-Organic Frameworks Combined with S- or N-Doped Carbon Dots - Maja D. Nešić; Iva A. Popović; Jelena Žakula; Lela Korićanac; Jelena Filipović Tričković; Ana Valenta Šobot; Maria Victoria Jiménez; Manuel Algarra; Tanja Dučić; Milutin Stepić (MDPI AG, 2024)
The literature data emphasize that nanoparticles might improve the beneficial effects of near-infrared light (NIR) on wound healing. This study investigates the mechanisms of the synergistic wound healing potential of NIR light and silver metal-organic frameworks combined with nitrogen- and sulfur-doped carbon dots (AgMOFsN-CDs and AgMOFsS-CDs, respectively), which was conducted by testing the fibroblasts viability, scratch assays, biochemical analysis, and synchrotron-based Fourier transform infrared (SR-FTIR) cell spectroscopy and imaging. Our findings reveal that the combined treatment of AgMOFsN-CDs and NIR light significantly increases cell viability to nearly 150% and promotes cell proliferation, with reduced interleukin-1 levels, suggesting an anti-inflammatory response. SR-FTIR spectroscopy shows this combined treatment results in unique protein alterations, including increased α-helix structures and reduced cross-β. Additionally, protein synthesis was enhanced upon the combined treatment. The likely mechanism behind the observed changes is the charge-specific interaction of N-CDs from the AgMOFsN-CDs with proteins, enhanced by NIR light due to the nanocomposite's optical characteristics. Remarkably, the complete wound closure in the in vitro scratch assay was achieved exclusively with the combined NIR and AgMOFsN-CDs treatment, demonstrating the promising application of combined AgMOFsN-CDs with NIR light photodynamic therapy in regenerative nanomedicine and tissue engineering.